Single observer speed sensorless field weakening control of two parallel motors - Suprajitno, Agus; Yusivar, Feri; Halim, Abdul (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Two induction motors with parallel connected stator windings supplied by a single inverter (single observer) with a field weakening control system. The objective of this study is to propose a torque production speed sensorless vector control technique for each parallel connected rotor by adding field weakening control to improve the performance of each motor and reducing the number of adaptive observers on each motor to a single observer. Design of a rotor flux-oriented control (RFOC) system. Simulation results with the C-MEX S-function of MATLAB/Simulink 2015b show that the proposed method works better and can be operated at speeds that exceed the nominal speed of the motor.